Tau Protein Biosensors in the Diagnosis of Neurodegenerative Diseases - Jafar Sadeghzadeh; Parviz Shahabi; Mehdi Farhoudi; Abbas Ebrahimi-Kalan; Ahmad Mobed; Kourosh Shahpasand (Tabriz University of Medical Sciences, 2023)
Tau protein plays a crucial role in diagnosing neurodegenerative diseases. However, performing an assay to detect tau protein on a nanoscale is a great challenge for early diagnosis of diseases. Enzyme-linked immunosorbent assay (ELISA), western-blotting, and molecular-based methods, e.g., PCR and real-time PCR, are the most widely used methods for detecting tau protein. These methods are subject to certain limitations: the need for advanced equipment, low sensitivity, and specificity, to name a few. With the above said, it is necessary to discover advanced and novel methods for monitoring tau protein. Counted among remarkable approaches adopted by researchers, biosensors can largely eliminate the difficulties and limitations associated with conventional methods. The main objective of the present study is to review the latest biosensors developed to detect the tau protein. Furthermore, the problems and limitations of conventional diagnosis methods were discussed in detail.